Optimising contextual factors in the practitioner-patient encounter in the management of osteoarthritis - Ismail, Ayah (2023)
Background Contextual factors (CFs) related to the patient, healthcare practitioners, and their therapeutic relationship are integral to the overall treatment effect of any given intervention. In osteoarthritis (OA), around 75% of the treatment effect is directly attributable to CFs. Identifying and understanding the role of CFs may encourage healthcare practitioners to develop and enhance the contextual aspects of care, and thus enhance the overall treatment benefit.